Terms of Trade in Bilingual and Multilingual Dictionaries - Sclafani, Marie-Denise (Verbum, 2021)
In this article, we analyze a corpus made up of two general French-Italian and Italian-French bilingual dictionaries and two multilingual dictionaries. We take into account, in particular, the macrostructure, the microstructure, the technical terminology and the phraseology of these dictionaries. Using a magnifying glass metaphorically, we focus on the treatment of the specialty language of commerce within the articles of the general bilingual dictionaries. With regard to plurilingual dictionaries, we try to show the lexicographical choices dictated by a requirement of extreme synthesis; the size of a dictionary, especially for schools, influences not only the convenience of consultation but also the price. The prodromes of the first business specialty language dictionaries represent an interesting corpus for understanding the first steps taken by lexicographers who decided to include specialty terminology in general bilingual dictionaries or to write multilingual business dictionaries.